Сопоставительная лексикография: русские и китайские словари новых слов - Golubeva-Monatkina, Nataliia; Hao, Chen (Wiener Slawistischer Almanach, 2023)
The article deals with a number of theoretical and practical problems of Russian and Chinese neography. In particular, it compares the approaches of Russian and Chinese linguists to the selection of vocabulary for inclusion in dictionaries of new words and describes the activities of neographers from both countries. The features of the macro- and micro-structures of Russian and Chinese dictionaries of new words are compared and the similarities and differences between explanatory dictionaries and dictionaries of new words are revealed. It is shown that the structure of the dictionaries of new words, on the one hand, and of explanatory dictionaries, on the other hand, are determined by the type of language, the nature of the writing systems, and national lexicographic traditions.